Numerical investigation with sensitivity study of MHD mixed convective hexagonal heat exchanger using TiO2–H2O nanofluid - Islam, Saiful; Islam, Muhammad Minarul; Rana, B.M.J.; Islam, Md Sirajul; Reza-E-Rabbi, Sk; Hossain, Md Shahadat; Rahman, M.M. (Results in engineering, 2023)
This ongoing study is carried out to analyze the thermal performance with sensitivity study of a mixed convective hexagonal heat exchanger containing TiO2–H2O nanofluid. Magnetic force is regarded to be horizontal while all surrounding walls are adiabatic. The finite element method is used to simulate the regulatory equations. For the first time, response surface methodology is used to analyze the sensitivity of independent factors on a hexagonal heat exchanger. The findings are depicted for four parameters, Reynolds number (10 ≤ Re ≤ 200), Richardson number (0.01 ≤ Ri ≤ 10), Hartmann number (0 ≤ Ha ≤ 100), and nanoparticle volume fraction (0 ≤ φ ≤ 0.1) against velocity distribution, average Nusselt number (Nuav), streamlines, isotherm lines, and heatlines. The results indicate that the growing value of Re and φ strengthen the thermal performance of nanofluid whereas increasing Ha causes it to decrease. Moreover, φ and Re have positive sensitivity to the Nuav while Ha has negative sensitivity. When Ha is maintained at 0, the optimal value of Nuav reaches when Re = 200 and φ = 0.1. The use of TiO2–H2O nanofluid improves the water's heat transmission ability to 17.69%. Finally, the results of this study may offer advice for creating an effective mixed convective heat exchanger. •The mixed convective hexagonal heat exchanger's heat transfer augmentation procedure is designed employing nanofluids.•The Galerkin weighted residual finite element method is applied to solving the involved governing equations.•Heatlines, streamlines, and isotherm contour visualizations for fluid flow and heat transmission are displayed.•There are a multitude of 2D and 3D contour plots that show the physical effects of significant parameters.•The sensitivity study of independent factors on average Nusselt number is explained using the response surface methodology.